Новый вид полевки Dotomys ondatroides sp. n. (Rodentia, Microtidae) из Котловннского местонахождения - Несин, B.А. (Вестник зоологии, 1981)
Dolomys ondatroides sp. n. differs from the previously known representatives of the genus in presence of cement in the incoming angles of molars and double complication of paraconid.The speciesis probably phylogenetically related to D. nehringi Kretzoi and is at the higherevolutionary level.